Knowledge about prevention ofHuman Immunodeficiency Virus sexual transmission in the community La Silsa - Emilio Vidal Borras; Marlín Páez Dominguez; Juana Fiallo Llanes (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: The Sexual Transmission Infections (STI) represents a serious problem worldwide, regarding health, economics and social issues. Objective: To determine the knowledge level about the prevention of sexual transmission of the Human Immunodeficiency Virus in a group of population between 15 - 49 years old in the community of La Silsa. Material and methods: Was performed an intervention study in the community of La Silsa, El Libertador municipality, Caracas, Venezuela about ,knowledge and changes of attitudes about the Human Immunodeficiency Virus, applying a questionnaire before and after the intervention. The study was designed in three stages: Diagnosis, Intervention, and Evaluation. Results: Was found out that the most frequent age group was from 15 to 19 years old (22.3 %) and the predominant gender was the feminine with 54.1 %. It was observed that 59.4 % has a basic grade level, with predominance of the feminine sex. After the study was achieved that 84.5 % have the knowledge about how to make protected sex, 100 % know which the suitable moment to put the condom is, and 98.7 % recognized the risk of infection from HIV. Conclusions: With the intervention, was positively achieve a change of the knowledge level about HIV, regarding: the performance of protected sex, the use of condom and the risk conditions for the infection by the HIV. Keywords: Protected sex, condom, Infection by HIV, knowledge, human immunodeficiency virus, risk, prevention, sexual transmission.